The Denominator Matters! Lessons from Large Database Research in Neonatology - Veeral N. Tolia; Reese H. Clark (MDPI AG, 2020)
Observational studies from large datasets are becoming more common in neonatology. In this review, we highlight the importance of the denominator in study design and interpretation including examples of bias from source data, weight-based categories, age-related bias, and diagnosis-based denominators.